Analysis of the effects of ownership-structure and social responsibility on profitability and company value - Hasanuddin, Rusdiah (Manunggal Halim Jaya, 2022)
In this study, we aim to investigate the effects of ownership structure on profitability, corporate social responsibility on profitability, ownership structure on firm value, corporate social responsibility on firm value, and profitability on the value of manufacturing companies listed on the stock exchange. We used a structural equation model (SEM) to analyze the data with the help of the AMOS program version 18. We found that (1) ownership structure has a positive and significant effect on company profitability (2) corporate social responsibility has a positive and significant effect on company profitability (4) Corporate social responsibility is positively and significantly correlated with firm value; and profitability is positively and significantly correlated with the value of manufacturing companies listed on the Indonesia Stock Exchange. The findings of this study back up the Legitimacy Theory and Stakeholders Theory that the legitimacy gap may be closed by legitimizing techniques such expanding social responsibility, in this instance a set of expenditures. Profitability is influenced by the ownership structure. This research demonstrates that the growing share ownership structure, including institutional, management, and public share ownership, indicates that the company's capital is becoming more powerful, and that if the capital is managed correctly, profitability will increase.